Temperature increase modifies susceptibility to Verticillium wilt in Medicago spp and may contribute to the emergence of more aggressive pathogenic strains - Sbeiti, Abed Al Latif; Mazurier, Mélanie; Ben, Cécile; Rickauer, Martina; Gentzbittel, Laurent (Frontiers in Plant Science, 2023)
Global warming is expected to have a direct impact on plant disease patterns in agro-eco-systems. However, few analyses report the effect of moderate temperature increase on disease severity due to soil-borne pathogens. For legumes, modifications of root plant-microbe interactions either mutualistic or pathogenic due to climate change may have dramatic effects. We investigated the effect of increasing temperature on the quantitative disease resistance to Verticillium spp., a major soil-borne fungal pathogen, in the model legume Medicago truncatula and the crop M. sativa. First, twelve pathogenic strains isolated from various geographical origin were characterized with regard to their in vitro growth and pathogenicity at 20°C, 25°C and 28°C. Most of them exhibited 25°C as the optimum temperature for in vitro parameters, and between 20°C and 25°C for pathogenicity. Second, a V. alfalfae strain was adapted to the higher temperature by experimental evolution, i.e. three rounds of UV mutagenesis and selection for pathogenicity at 28°C on a susceptible M. truncatula genotype. Inoculation of monospore isolates of these mutants on resistant and susceptible M. truncatula accessions revealed that at 28°C they were all more aggressive than the wild type strain, and that some had acquired the ability to cause disease on resistant genotype. Third, one mutant strain was selected for further studies of the effect of temperature increase on the response of M. truncatula and M. sativa (cultivated alfalfa). The response of seven contrasted M. truncatula genotypes and three alfalfa varieties to root inoculation was followed using disease severity and plant colonization, at 20°C, 25°C and 28°C. With increasing temperature, some lines switched from resistant (no symptoms, no fungus in the tissues) to tolerant (no symptoms but fungal growth into the tissues) phenotypes, or from partially resistant to susceptible. Further studies in greenhouse evidence the reduction in plant fitness due to disease in susceptible lines. We thus report that root pathogenic interactions are affected by anticipated global warming, with trends towards increased plant susceptibility and larger virulence for hot-adapted strains. New threats due to hot-adapted strains of soil-borne pathogens, with possibly wider host range and increased aggressiveness, might occur.